Hermann von Wartberge (Warburg) and his Origins. New Research and Outcomes - Janiec, Jerzy (Studia Europaea Gnesnensia, 2016)
The main aim of this paper is to present the findings of the latest, authorial indepth research concerning the ancestry of a chaplain and chronicler to the masters of the Livonian branch of the Teutonic Order, Hermann von Wartberge, who lived in the 14th century. The author successively addresses and attempts to fill the gaps regarding this historical figure using primary and secondary sources. The main conclusion is that Hermann might have originated from the old Mecklenburgian house of von Warburg.